2012 IEEE 12th International Conference on Data Mining 2012
DOI: 10.1109/icdm.2012.86
|View full text |Cite
|
Sign up to set email alerts
|

Mining Permission Request Patterns from Android and Facebook Applications

Abstract: Android and Facebook provide third-party applications with access to users' private data and the ability to perform potentially sensitive operations (e.g., post to a user's wall or place phone calls). As a security measure, these platforms restrict applications' privileges with permission systems: users must approve the permissions requested by applications before the applications can make privacy-or security-relevant API calls. However, recent studies have shown that users often do not understand permission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 13 publications
(17 reference statements)
1
54
0
Order By: Relevance
“…One of their key observations is that the set of dangerous-level permissions always outnumbers other permission types in all versions of the Android platform and it is still growing. Frank et al studied the permission request patterns of Android apps using pattern mining technique [22]. They tried to relate the permission request pattern with the app's reputation which can be served as an indicator of app quality.…”
Section: Related Workmentioning
confidence: 99%
“…One of their key observations is that the set of dangerous-level permissions always outnumbers other permission types in all versions of the Android platform and it is still growing. Frank et al studied the permission request patterns of Android apps using pattern mining technique [22]. They tried to relate the permission request pattern with the app's reputation which can be served as an indicator of app quality.…”
Section: Related Workmentioning
confidence: 99%
“…Chia et al showed that community ratings are not reliable and that most applications request more permissions than needed [2]. Frank et al extended this work, showing that Facebook permissions follow a predefined pattern and that malicious applications deviate from it [4]. Finally, Xia et al…”
Section: Related Researchmentioning
confidence: 87%
“…We then automate the process of application installation based on the Selenium WebDriver. 4 In particular, using several different Facebook accounts with distinctly different user profiles, we install and accept the requested permissions for each of the 997 applications. To monitor the application behavior, we use a modified version of a Firefox plug-in [7], allowing us to record all the HTTP and HTTPS traffic.…”
Section: Methodsmentioning
confidence: 99%
“…A concern with these approaches is false positives stemming from the coarse-grained nature of permissions and the highly common nature of benign apps to over-claim their set of required permissions. Mario et al [24] presented their studies of permission request patterns of Android and Facebook applications.…”
Section: Evaluation Resultsmentioning
confidence: 99%